Faktor-Faktor Pendorong Polandia Menentang The European Green Deal Tahun 2019-2023 - Fitri, Nela Elfita; Apriwan; Diah Anggraini Austin (Palito, 2025)
In 2019, the European Commission established an ambitious policy initiative regarding environmental change issues called the European Green Deal. The aim of this policy is to achieve zero emissions by 2050 and make Europe as the first climate neutral continent by that year. All member states had to adopt the goals, and Poland was the only member state opposes that policy. This research aims to explain the factors driving Poland's opposition to the European Green Deal in 2019-2023. These driving factors will be explained using the theory of Foreign Policy Decision Making by William D. Coplin. Coplin explained that a country's decisions can be influenced by several determinant factors, namely the international context, domestic politics, and economic and military stability. This research uses a qualitative approach with descriptive analysis research type. This research found that Poland's decision to oppose The European Green Deal was caused by Poland's energy and economic security, international dynamics and euroskepticism, as well as Poland’s domestic political instability.